Uncommon Dorsal Radiocarpal Fracture Dislocation Complicated With Median Nerve Palsy: Case Report, Review of the Literature, and a New Classification System Guiding the Management - Hing-Cheong Wong; Hin-Keung Wong; Kam-Yiu Wong (Journal of Orthopaedics, Trauma and Rehabilitation, 2012)
We report the case of a 36-year-old lorry driver who sustained left dorsal radiocarpal fracture dislocation and left median nerve injury in a traffic accident in 2010. Emergency operation of closed reduction, cross-wrist-bridging external fixation, percutaneous transradial styloid Kirschner wire fixation, decompression of left median nerve, and repair of the partially torn palmar radiocarpal ligament were performed under general anaesthesia. Because of the persistent depressed dorsal articular rim fracture of left distal radius, another operation of open reduction, corticocancellous bone grafting, and dorsal buttress plating was performed 5 days after the initial operation. Six months after the operation, the patient enjoyed good range of wrist motion but weak twisting power, especially in supination. There was no radiological feature of radiocarpal subluxation.